UPAYA LEMBAGA STUDI ISLAM DALAM MENINGKATKAN PEMAHAMAN KEISLAMAN PADA MAHASISWA (Studi Kasus di Lembaga Bahasa Arab dan Studi Islam Ma`had Thalhah bin Ubaidillah Palu) - Khaeruddin Yusuf (ISTIQRA, 2014)
This study discusses the efforts of the islamic institute in improving the students` Islamic Understanding in the Institute of Arabic Language and Islamic Studies Ma'had Talhah bin Ubaidillah Palu. This research using the descriptive qualitative approach to understand and describe the phenomena that occur in an effort to increase the students` islamic understanding at the Institute of Arabic and Islamic Ma'had Talhah bin Ubaidillah Palu. The efforts made by the Institute of Arabic and Islamic in improving student`islamic understanding is through formal and non-formal education. Formal education in question is revamping the curriculum through Arabic and Islamic Studies while non-formal is through extracurricular activities, namely, speech exercise, scientific seminar, weekly praying, ramadhan tour, and propagation program. This study recommended that the need for methodological improvements through the application of alternative methods, the conventional curriculum renewal based on the contents of the Competency-Based Curriculum (CBC) and it is expected that students not only know the teachings of Islam in theory, but can open up horizons, increase understanding and awareness as a muslims who are able to apply the values of Islam in daily life